Membangun Strategi Keunggulan Bersaing Pada Perusahaan X - Hanif Furqon Abdurrahman; Zulkifli; Miranda W, Agustinus (SEKOLAH PASCASARJANA PRESS, 2025)
The focus of this thesis is how a company makes strategic planning for a trading business, with the object of research being Company X's business which is classified as a small-medium business in order to develop and maintain competitive advantage in times of disruption or changing conditions through designing the right strategy. This research is a qualitative research with a problem approach through descriptive analysis, regarding Building a Competitive Advantage Strategy in Company X 2023 – 2028. The sampling technique used purposive with Forum Group Discussion followed by qualitative analysis using TOWS, IFE, EFE, CPM and QSPM. The research results obtained are an alternative strategy